Chronic Nocardia cyriacigeorgica Periprosthetic Knee Infection Successfully Treated with a Two-Stage Revision: A Case Report. Issue 4 (October 2017) - Hadeed, Michael M.; MacDonell, J. Ryan; Dempsey, Ian J.; Moore, Christopher C.; Browne, James A.
Abstract : Case: We report the successful treatment of a Nocardia cyriacigeorgica periprosthetic joint infection (PJI) that occurred at the site of a total knee arthroplasty. To our knowledge, this organism has not previously been reported in the literature as a cause of PJI. Given the need for a prolonged duration of treatment for this organism (a minimum of 6 to 12 months), modifications to the standard 2-stage revision were made in consultation with infectious-disease specialists. Conclusion: PJI is a devastating complication that leads to substantial patient morbidity and utilization of health-care resources. As the number of PJIs continues to rise, new and increasingly challenging infections are being encountered more frequently. In the case described here, the second stage of the revision was delayed for 6 months and antibiotics were continued for 7 months after the second operation, for a total of 13 months of antibiotic treatment. The present report provides a possible treatment plan for patients infected with durable bacteria similar to N. cyriacigeorgica.